Environment Based Ecosystem Thematic Teaching Materials: Using Problem Based Learning to Improve Learning Effectiveness - Bintang Astama, Putra; Minsih (Universitas Pendidikan Ganesha, 2023)
Learning outcomes in ecosystem thematic teaching materials for fifth grade students is far from satisfactory. In thematic learning, teachers still use conventional models and have not implemented appropriate learning models for thematic subjects, so the average score in these subjects is still very low. The purpose of this study was to analyze the effectiveness of the Problem Based Learning model for student learning outcomes in thematic ecosystem material for five grade primary school. This type of research is quantitative with True Experimental Design in the school environment. This study consist of Pre-test-Post-test Control Group Design. The samples taken were 6 VA class students as the experimental class and 6 VB class students as the control class using the simple random sampling technique. The results showed that the average post-test score for the experimental class was higher, namely in the VA class. It was concluded that the Problem Based Learning Model was effective on student learning outcomes in class V ecosystem thematic material.